Penilaian Status Kesuburan Tanah pada Lahan Pascatambang di Areal PT. Trubaindo Coal Mining Kabupaten Kutai Barat - Dhian Dwi Ramadhana; Donny Donantho; Ria Rachel Paranoan (Jurnal Agroekoteknologi Tropika Lembab, 2019)
The aim of study is to assessing soil fertility status on post-mining land in the area PT. Trubaindo Coal Mining, West Kutai, East Kalimantan Province. Assessment of soil fertility is determined based on the method developed by Bogor Soil Research Institute (2005), that is by using descriptive comparative method where the data from the soil analysis are then compared with the standard criteria for soil chemical properties and the criteria for assessing soil fertility status developed. The results showed the status of the average value of the soil pH 4.62 (acid), C-Organic 1.08% (low), Nitrogen 0.09% (very low), Phosphorus 2.15 ppm (very low), Pottasium 65.53 ppm (very high), Cation Exchange Capacity 6.29 meq100g-1 (low), and Base Saturation 44,83 % (moderate). Soil of post mining land in PT. Trubaindo Coal Mining have a“low” fertility status, so further management action is needed to improve soil fertility status.